Chris R. Hawes (1953-2019) - Robinson, David G. (Trends in plant science, 2019)
Chris Hawes died on 4 July 2019. He was an excellent microscopist who will be particularly remembered for his groundbreaking observations on Golgi and endoplasmic reticulum (ER) structure and function. His passing is a great loss for plant cell biology.